A Diagnostic Algorithm for Detection of Antibodies to Influenza A Viruses in Dogs in Italy (2006–2008) - De Benedictis, Paola (2010)
Since 2004, there have been several reports of Influenza A virus (FLUAV) infection in dogs. Dogs have been infected with equine influenza H3N8, avian influenza H3N2 and H5N1, and the pandemic H1N1 virus. Because of recent avian and equine influenza outbreaks in Italy, the objectives of the present study were to estimate the level of exposure of Italian dogs to influenza A viruses and to assess a diagnostic algorithm for detection of FLUAV exposure in dogs. Sera collected from 6,858 dogs from 2006 to 2008 were screened in a competitive enzyme-linked immunosorbent assay (cELISA) for antibodies to the highly conserved influenza A nucleoprotein. Samples positive in the cELISA were confirmed by testing in hemagglutination inhibition (HI) and fluorescent antibody test (FAT). Two seropositive dogs had antibodies to H3 hemagglutinin proteins, consistent with exposure to recent canine and equine subtype H3N8 viruses. Using a Bayesian model, the sensitivity and specificity of the cELISA were estimated as 93.98% (probability intervals [PI]: 81.67–99.08%) and 98.71% (PI: 98.43–98.96%), respectively. After accounting for the imperfect sensitivity and specificity of the cELISA, the Bayesian posterior prevalence of FLUAV exposure among tested Italian dogs was 0.5% (PI: 0.1–1.4%). The study results indicate that screening with a cELISA for influenza A nucleoprotein antibody, followed by confirmatory testing with HI and/or FAT, is a highly sensitive and highly specific approach for diagnosing FLUAV exposure in dogs.